TGF-β2 silencing to target biliary-derived liver diseases. Issue 9 (28th January 2020) - Dropmann, Anne; Dooley, Steven; Dewidar, Bedair; Hammad, Seddik; Dediulia, Tatjana; Werle, Julia; Hartwig, Vanessa; Ghafoory, Shahrouz; Woelfl, Stefan; Korhonen, Hanna; Janicot, Michel; Wosikowski, Katja; et al.
Abstract : Objective: TGF-β2 (TGF-β, transforming growth factor beta), the less-investigated sibling of TGF-β1, is deregulated in rodent and human liver diseases. Former data from bile duct ligated and MDR2 knockout (KO) mouse models for human cholestatic liver disease suggested an involvement of TGF-β2 in biliary-derived liver diseases. Design: As we also found upregulated TGFB2 in liver tissue of patients with primary sclerosing cholangitis (PSC) and primary biliary cholangitis (PBC), we now fathomed the positive prospects of targeting TGF-β2 in early stage biliary liver disease using the MDR2-KO mice. Specifically, the influence of TgfB2 silencing on the fibrotic and inflammatory niche was analysed on molecular, cellular and tissue levels. Results: TgfB2 -induced expression of fibrotic genes in cholangiocytes and hepatic stellate cellswas detected. TgfB2 expression in MDR2-KO mice was blunted using TgfB2 -directed antisense oligonucleotides (AON). Upon AON treatment, reduced collagen deposition, hydroxyproline content and αSMA expression as well as induced PparG expression reflected a significant reduction of fibrogenesis without adverse effects on healthy livers. Expression analyses of fibrotic and inflammatory genes revealed AON-specific regulatory effects on Ccl3, Ccl4, Ccl5, Mki67 and Notch3 expression. Further, AON treatment of MDR2-KO mice increased tissue infiltration by F4/80-positive cells including eosinophils, whereas the number of CD45-positive inflammatory cells decreased. In line, TGFB2 and CD45 expression correlated positively in PSC/PBC patients and localised in similar areas of the diseased liver tissue. Conclusions: Taken together, our data suggest a new mechanistic explanation for amelioration of fibrogenesis by TGF-β2 silencing and provide a direct rationale for TGF-β2-directed drug development.